2019
DOI: 10.1038/s41586-019-1285-1
|View full text |Cite
|
Sign up to set email alerts
|

Migrant memory B cells secrete luminal antibody in the vagina

Abstract: Antibodies secreted into the mucosal barriers serve to protect the host from a variety of pathogens, and are the basis for successful vaccines1. In type I mucosa such as the intestinal tract, dimeric IgA secreted by local plasma cells is transported through polymeric Ig receptors (pIgR)2, and mediates robust protection against viruses in the vaccinees3,4. However, due to the paucity of pIgR and plasma cells, how and whether antibodies are delivered to the type II mucosa represented by the lower female reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 33 publications
2
74
0
Order By: Relevance
“…Tph cells appear well equipped to mediate these interactions, particularly in chronically inflamed peripheral tissues, where they may function to promote local accumulation of antibody-secreting cells (21). The ability of Tph cells to stimulate differentiation of memory, rather than naive, B cells in vitro is consistent with the idea that Tph cells may primarily interact with activated or memory B cells, which are more likely than naive B cells to traffic through inflamed tissues (41). The strong correlation between Tph cells, but not Tfh cells, and CD11c + B cells in circulation further supports that idea that Tph cells may play a unique role in autoimmune pathology.…”
Section: Discussionsupporting
confidence: 61%
“…Tph cells appear well equipped to mediate these interactions, particularly in chronically inflamed peripheral tissues, where they may function to promote local accumulation of antibody-secreting cells (21). The ability of Tph cells to stimulate differentiation of memory, rather than naive, B cells in vitro is consistent with the idea that Tph cells may primarily interact with activated or memory B cells, which are more likely than naive B cells to traffic through inflamed tissues (41). The strong correlation between Tph cells, but not Tfh cells, and CD11c + B cells in circulation further supports that idea that Tph cells may play a unique role in autoimmune pathology.…”
Section: Discussionsupporting
confidence: 61%
“…When it comes to acquired immunity to virus, which mainly involves memory B cells, memory CD8 ± T cells, and memory T cells, then their team continues to study that circulating memory B cells are recruited to the vaginal mucosa in a CXCR3-dependent manner and secrete virus-specific IgG2b, IgG2c, and IgA that can be transported by FcRn into the vaginal lumen as a result of a rapid and strong immune defense response (113,114). On the other hand, memory CD8± T cells in the vaginal mucosa are considered to be the most important immune cells against virus (115), histocompatibility complex class I (MHC I) transited by CD301b± DCs, and NK cells can stimulate CD8± T to secrete IFN-γ, which can resist viruses (116).…”
Section: Efficient Immunity To Virus Infection During Pregnancymentioning
confidence: 99%
“…This response can be enhanced by DCs and B cells (117). Additionally, CD4 tissue-resident memory T cells can also be stimulated and secrete IFN-γ, which causes expression of chemokines, including CXCL9 and CXCL10 (113). There is a specific example about IFNs resisting virus, that is, ZIKV, which can be transmitted sexually between humans.…”
Section: Efficient Immunity To Virus Infection During Pregnancymentioning
confidence: 99%
“…NGS approaches for generating immune repertoires commonly begin with genomic DNA or mRNA and produce high-depth bulk repertoires of unpaired immunoglobulin or T cell receptor V(D)J sequences (33)(34)(35). Recent approaches use single-cell isolation techniques with highthroughput sequencing to construct repertoires, sometimes with paired gene expression (36)(37)(38)(39). These include studies on tumor-infiltrating lymphocytes from cancer biopsies, infiltrates from the brain of mice and B cells from the spleen after vaccination in mice; no such studies have investigated the circulating B cell repertoire in patients with autoimmune disease thusfar (37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…Recent approaches use single-cell isolation techniques with highthroughput sequencing to construct repertoires, sometimes with paired gene expression (36)(37)(38)(39). These include studies on tumor-infiltrating lymphocytes from cancer biopsies, infiltrates from the brain of mice and B cells from the spleen after vaccination in mice; no such studies have investigated the circulating B cell repertoire in patients with autoimmune disease thusfar (37)(38)(39). Previous immune repertoire studies of BCDT have identified persistent expanded clones and associations between clonality and responder status, and single-cell transcriptome studies have recapitulated flow cytometry results showing increased frequencies of antigen-experienced B cells at the peak of depletion (32,(40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%